Lung Adenocarcinoma in a Patient with Plasmacytoma. (22nd December 2013) - Hiasa, Atsunori; Nakase, Kazunori; Fukutome, Kazuo; Nomura, Hideki; Ueno, Setsuko; Mizuno, Toshiro; Katayama, Naoyuki; Takeuchi, Toshiaki
Abstract : An increased risk of second malignancy is well recognized in patients treated for plasma cell neoplasms. However, second solid tumor is very rare in such patients. We report a case of a 68-year-old woman with plasmacytoma who developed lung adenocarcinoma.